2002
DOI: 10.1007/s001980200010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transdermal Estradiol Delivered by a Matrix Patch on Bone Density in Hysterectomized, Postmenopausal Women: A 2-year Placebo-Controlled Trial

Abstract: This 2-year, double-masked, randomized, placebo-controlled trial was designed to evaluate the safety and efficacy in preventing bone loss in postmenopausal women of two doses of transdermal 17betaestradiol (estradiol) delivered by a matrix patch, compared with placebo. One hundred and sixty healthy, hysterectomized postmenopausal volunteers aged 40-60 years with serum estradiol levels < 20 pg/ml were started on treatment at four centers in The Netherlands. Every 6 months, bone mineral density (BMD) was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 19 publications
(24 reference statements)
2
7
0
Order By: Relevance
“…The difference between treatment and placebo after 1 year of treatment is 3.8%. This is similar to the differences seen in studies of today's standard doses [32] of oestradiol, 1 mg per day oral (in sequential association with dydrogesterone) [27] or 50 g transdermal oestradiol per day oestradiol transdermal in hysterectomised women [33,34]. Thus, neither the progestogen nor its mode administration as used in this study seems to modulate to a noticeable extent the effect of oestradiol on BMD.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The difference between treatment and placebo after 1 year of treatment is 3.8%. This is similar to the differences seen in studies of today's standard doses [32] of oestradiol, 1 mg per day oral (in sequential association with dydrogesterone) [27] or 50 g transdermal oestradiol per day oestradiol transdermal in hysterectomised women [33,34]. Thus, neither the progestogen nor its mode administration as used in this study seems to modulate to a noticeable extent the effect of oestradiol on BMD.…”
Section: Discussionsupporting
confidence: 86%
“…The proportion of BMD losers (18.5%) in the active treatment group is comparable to, e.g. the fraction of 'losers' (16.3%) upon treatment with 50 g per day transdermal oestradiol [33]. The median loss in losers on active treatment is smaller than the median loss on placebo in this and the trial of transdermal E2 [33].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Arrenbrecht and Boermans reported that transdermal estradiol in a dose of 50 mg/d significantly increased BMD in the lumbar spine and hip; a dose of 100 mg/d provided only a marginally increased benefit that was offset by a more pronounced side-effect profile. 63 Estrogen monotherapy versus estrogen/progestogen combinations Although it has become standard practice to include a progestin when treating intact postmenopausal women with estrogen, the origin of this practice dates from studies using doses of estrogen higher than those currently utilized. The role of estrogen in the development and course of (receptor positive) endometrioid endometrial cancer, as opposed to estrogenÕs lack of effect on (receptor negative) papilloserous endometrial cancer had not come to light 16 and the side effects of synthetic progestins not yet appreciated.…”
Section: Bone Sparing By Transdermal Estradiolmentioning
confidence: 99%